PEMODELAN CONTINUANCE INTENTION DALAM KASUS PENGGUNAAN DOMPET DIGITAL DI KALANGAN MAHASISWA - Desribeth Palullungan (Universitas Bunda Mulia, 2022)
The successful use of an information system or technology does not only focus on the perception of the first use (initial use), but also on the sustainability of its use (continuance intention). Continuance intention is a behavior that shown by consumer to continue to use an information system or technology. The purpose of this study was to determine the factors that influence continuance intention to use digital wallets among students. The results obtained from this study can be used by interested companies, such as e-commerce, internet service providers, retailers, and banks to predict consumer behavior in conducting transactions so that they can provide transaction services according to the needs and desires of consumers. The data collection method in this study was a questionnaire with the help of google form. The analysis technique used is Structural Equetion Modeling (SEM) with the help of PLS-SEM 4 software. The model developed is based on the Expectation Confirmation Model (ECM) by adding information quality and service quality variables. By the 9 hypotheses built, there is 1 rejected hypothesis while the other 8 hypotheses are accepted. Quality service variable has no effect on consumers' initial trust to use digital wallets. The Satisfaction variable motivates users to continue using digital wallets.